The travelling museum of Barberton : making dialogue work in a rural community museum. - Stone, Kristy (My University, 2013)
Cotemporary museum theory calls for dialogue as a means of making museums multi-‐ vocal and representative of larger audiences. Dialogue is seen to be a break with prior modernist practices and epistemology. However, in most cases what is meant by dialogue and how to implement it is not made clear. I proposed using the Community of Enquiry Approach to dialogue in the development of the Travelling Museum. The Travelling Museum is a community museum based at ‘The Centre’ on the land of the Swazi chief in Emjindini. I was concerned that labelling the community and associating the museum with the chief could perpetuate essentialised ideas of what it meant to be Swazi. I was also conscious of not wanting to be the ‘outsider expert’ and for the museum to be developed by the community it was intended for. It was for these reasons that I decided to employ the ideas of dialogue. While implementing dialogue through the Community of Enquiry, I started to question whether this method of dialogue could become normative, and whether it excluded or silenced certain members. I wanted to locate this approach to dialogue on a larger theoretical base, in order to understand how dialogue challenges and departs from modernism and moves into postmodernism. In order to do this in the Report I explore postmodern and modern theories of knowledge and difference. My research method is to use critical incidents. These are moments of noticing or jarring in my practice, which when interpreted allow me to interrogate theory and practice. The first incident questions my openness to the other where I raise concerns of relativism. The second and third incidents address issues of power and access in museums. I conclude by recommending a new role for the museum. No longer in a role of cultural authority, museums can take on the new role of artist. As an artist the museum can be multi-‐partial and act as social commentator, provocateur and catalyst for change (Gogan, 2005, p.60 ).
Keywords: Community museums--South Africa--Barberton.; Traveling exhibitions--South Africa.; Dialogue.; Swazi (African people)--Social life and customs.